The Intersection of Mental Health, Law, and Rehabilitation - Nursyakinah, Kintan Berlina; Mulyana, Aji; Amalia, Mia (Politeknik Ilmu Pemasyarakatan, 2023)
Prisoners are people who are serving a sentence or criminal period in a correctional institution, but the human rights of prisoners must also be protected. However, prisoners are also part of those who have rights as human beings, including the right to live life, the right to receive welfare, and also have the right to obtain health services. The rights of prisoners are even regulated in law number 22 of 2022 concerning correctional facilities. In addition to physical health, there is mental health that is vulnerable to threats to prisoners. The importance of mental health in relation to the law relates to several issues, including the difficulty of individuals to provide accurate testimony, the consideration of mental capacity in the judicial process, as well as the protection of the rights of mentally ill individuals. This research explores the intersection between mental health, law, and rehabilitation in the context of prisoners. The main focus is to evaluate the challenges that arise in fulfilling prisoners' mental health service rights through the existing legal and rehabilitation systems. Through an interdisciplinary approach, this research seeks an in-depth understanding of how legal factors and the detention environment can affect the mental health of inmates. This approach includes prevention, diagnosis and intervention measures covering medical, psychological, social and legal aspects. The research seeks to provide a basis for policy change that supports the rights of individuals with mental illness, promotes fairness in the justice system, and reduces stigmatisation associated with mental health in legal contexts.